Nearby grandmother enhances calf survival and reproduction in Asian elephants - Mirkka Lahdenperä; Khyne U. Mar; Virpi Lummaa (NATURE PUBLISHING GROUP, 2022)
Usually animals reproduce into old age, but a few species such as humans and killer whales can live decades after their last reproduction. The grandmother hypothesis proposes that such life-history evolved through older females switching to invest in their existing (grand) offspring, thereby increasing their inclusive fitness and selection for post-reproductive lifespan. However, positive grandmother effects are also found in non-menopausal taxa, but evidence of their associated fitness effects is rare and only a few tests of the hypothesis in such species exist. Here we investigate the grandmother effects in Asian elephants. Using a multigenerational demographic dataset on semi-captive elephants in Myanmar, we found that grandcalves from young mothers (< 20 years) had 8 times lower mortality risk if the grandmother resided with her grandcalf compared to grandmothers residing elsewhere. Resident grandmothers also decreased their daughters' inter-birth intervals by one year. In contrast to the hypothesis predictions, the grandmother's own reproductive status did not modify such grandmother benefits. That elephant grandmothers increased their inclusive fitness by enhancing their daughter's reproductive rate and success irrespective of their own reproductive status suggests that fitness-enhancing grandmaternal effects are widespread, and challenge the view that grandmother effects alone select for menopause coupled with long post-reproductive lifespan.